2022
DOI: 10.3390/antibiotics11121766
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics as Adjunctive Therapy in the Non-Surgical Treatment of Peri-Implantitis: A Systematic Review and Meta-Analysis

Abstract: The role of antibiotics as adjunctive therapy in the non-surgical treatment of peri-implantitis is uncertain. The aim of this systematic review of randomized controlled trials was to assess the efficacy of antibiotic therapy, local or systemic, as an adjunctive to the non-surgical therapy of peri-implantitis. Primary outcomes were: implant success rate and complications, changes in radiographic bone level, probing pocket depth (PPD), probing attachment level (PAL), bleeding on probing (BOP) and peri-implantiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…Most of these reviews included the same RCTs, with only slight variation of the focused question among different studies. Overall, these systematic reviews included from 4 to 26 studies 16,57–69 and showed contradictory conclusions in terms of recommending 65 or not 66 the use of adjunctive antimicrobials to treat peri‐implantitis. In this sense, a scoping review such as this one critically discussing the literature on this topic is helpful to guide clinical decision and future studies.…”
Section: Discussion Clinical Application and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these reviews included the same RCTs, with only slight variation of the focused question among different studies. Overall, these systematic reviews included from 4 to 26 studies 16,57–69 and showed contradictory conclusions in terms of recommending 65 or not 66 the use of adjunctive antimicrobials to treat peri‐implantitis. In this sense, a scoping review such as this one critically discussing the literature on this topic is helpful to guide clinical decision and future studies.…”
Section: Discussion Clinical Application and Future Perspectivesmentioning
confidence: 99%
“…The main strength of this study was that for the first time, it provided a thorough evaluation of the clinical and microbiological outcomes of locally and systemically delivered antibiotics as adjuncts to the surgical and nonsurgical debridement of implants affected by periimplantitis. While recent systematic reviews have assessed the benefits of antibiotics for the treatment of peri-implantitis, 16,58,63,65,66,84 none of them provided data for different types of antibiotic delivery or for the effects of these agents in changing the submucosal microbiome. We have recently highlighted that the scoping reviews assessing laboratory data are useful scientific tools still underused in dentistry.…”
Section: Discussion Clinical Application and Future Perspectivesmentioning
confidence: 99%
“…Aj z tohto dôvodu sa použitie MAP s obľubou kombinuje s ďalšou, podpornou terapiou. Antibiotiká ako doplnková terapia pri liečbe peri-implantitídy ukazujú veľmi sľubné výsledky a je popísané výraznejšie zlepšenie hodnôt klinických indexov v porovnaní s mechanickou terapiou samotnou [24][25][26].…”
Section: úVodunclassified